The Mediating Role of Organizational Commitment in Affecting the Emotional Intelligence on Employees’ Performance in Private Universities - Milhem, Sami; Harahsheh, Alaa; Abu Ghouch, Sanaa; Abu Hussain, Alharith; Kanaan, Raed (Dirasat: Educational Sciences, 2020)
This study aimed to identify the mediating of organizational commitment in the effect of emotional intelligence on employees’ performance in private universities. The study population consists of (496) in Jordanian university students. The researcher used descriptive approach in this study and the questionnaire was adopted as a tool for study and data collection. The research questionnaires were analyzed using a number of statistical methods by statistical programs for social sciences (SPSS). The study concluded that there was a statistically significant effect at the level of (α = 0.05) of the mediating of organizational commitment in the effect of emotional intelligence (Emotional knowledge, self-awareness, motivation, empathy, social skills) on employees’ performance in their dimensions (Accuracy of achievement, creativity, ability to learn, regularity in work). The results showed a statistically significant effect of critical success factors for the mediating of organizational commitment in Jordanian university students. The study concluded that Jordanian universities should adopt an effective vision in highlighting the intermediate role of organizational commitment in the impact of emotional intelligence on the performance of employees in Jordanian private universities.